2022
DOI: 10.1038/s41598-022-08230-z
|View full text |Cite
|
Sign up to set email alerts
|

Shared antibiotic resistance and virulence genes in Staphylococcus aureus from diverse animal hosts

Abstract: The emergence of methicillin-resistant Staphylococcus aureus (MRSA) poses an important threat in human and animal health. In this study, we ask whether resistance and virulence genes in S. aureus are homogeneously distributed or constrained by different animal hosts. We carried out whole genome sequencing of 114 S. aureus isolates from ten species of animals sampled from four New England states (USA) in 2017–2019. The majority of the isolates came from cats, cows and dogs. The maximum likelihood phylogenetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 68 publications
4
20
1
4
Order By: Relevance
“…Staphylococcus aureus is a ubiquitous organism that has the ability to colonize and infect humans and a wide range of other mammals and birds, with each host representing a distinct ecological niche [ 1 ]. S. aureus can cause nosocomial and community infections in humans which can range from skin and soft tissue infections to life-threatening infections such as endocarditis and bacteremia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus is a ubiquitous organism that has the ability to colonize and infect humans and a wide range of other mammals and birds, with each host representing a distinct ecological niche [ 1 ]. S. aureus can cause nosocomial and community infections in humans which can range from skin and soft tissue infections to life-threatening infections such as endocarditis and bacteremia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as in humans, S. aureus can also cause various types of infections in animals, the most common of which are mastitis in bovine, skin and soft tissue infections in companion animals, septic arthritis in poultry, abscesses in rabbits among others [ 15 , 16 , 17 , 18 ]. S. aureus from animals are also known to carry several antimicrobial resistance determinants that can be transferred to humans and other animals [ 1 ]. S. aureus can be grouped into many different genetic lineages defined by molecular typing methods, and it has been shown that some S. aureus lineages tend to be more prevalent in specific types of infections or be host-specific [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a dairy herd has clinical mastitis (animals with obvious disease) or subclinical mastitis (animals with no obvious signs) milk contamination and discard rates increase, productivity decreases, antimicrobial treatment costs increase, and animals may have to be culled prematurely ( Exel et al, 2022 ). Zoonotic transmission of S. aureus has been widely documented ( Patel et al, 2021 ) and characterization of sequence types (STs) helps to elucidate strain relationships and epidemiology, as well as gene transfer amongst strains from different hosts ( Bruce et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…O uso inadequado dos antimicrobianos na medicina humana e veterinária colabora de forma significativa para a seleção de bactérias com genes de resistência a antimicrobianos (Watkins e Bonomo, 2020), o que torna a realização do antibiograma essencial para determinar uma abordagem terapêutica mais adequada para na clínica do paciente e eficaz como medida para evitar a seleção de bactérias resistentes (Duque-Estrada et al, 2003;Pedersen et al, 2007). O monitoramento molecular de genes de resistência é uma importante ferramenta epidemiológica para determinar os patógenos em animais de companhia, pois dimensiona cepas que possam causar riscos à saúde humana e animal como Staphylococcus resistente à meticilina (Bruce et al, 2022).…”
Section: Discussionunclassified